On the Mechanical Properties of Ultrananocrystalline Diamond/Amorphous Carbon Nanocomposite Films - Popov, Cyril (Micro and Nanosystems, 2014)
Microwave plasma chemical vapor deposition from CH4/N2 mixtures has been used for the preparation of ultrananocrystalline diamond/amorphous carbon (UNCD/a-C) composite films on different substrates. We characterized these films with respect to their mechanical properties by nano-indentation, nano-scratch tests and micro- and nanotribometer measurements. The hardness and the Young's modulus of UNCD/a-C on Si, polycrystalline diamond (PCD) and c-BN determined by nanoindentations were on the order of 34-40 GPa and 325-390 GPa, respectively, higher than those of films on TiN. The best adhesion determined by Nano-Scratch tests was observed for the UNCD/a-C films on TiN, most probably as a result of the better adhesion between the silicon substrate and the intermediate layer. The tribotest measurements revealed that the UNCD/a-C films possess friction coefficient below 0.01 in humid air while it increases in dry oxygen, nitrogen and argon atmospheres. Although the presence of an amorphous matrix reduces the hardness by a factor of 2.5-3 in comparison with the monocrystalline diamond, it may be of advantage for the tribological performance of wear protecting coatings by improving their toughness.
Keywords: ultrananocrystalline diamond/amorphous carbon composite films